Vigorous rootstocks improve yields and increase fruit sizes in grafted fresh market tomatoes - Ingram, Thomas W.; Sharpe, Suzette; Trandel, Marlee; Perkins-Veazie, Penelope; Louws, Frank J.; Meadows, Inga (Frontiers in Horticulture, 2022)
Grafting high yielding tomato cultivars (Solanum lycopersicum L.) onto vigorous rootstocks can increase marketable yields, but questions remain regarding optimal cultural and growing conditions such as pinching and plant spacing. This study addressed some of the dynamics between grafted plants and cultural practices. Two scions, ‘Tasti-Lee’(TL) and ‘Mountain Fresh Plus’ (MFP) were grafted onto each of three rootstocks, ‘Beaufort’, ‘Arnold’, and ‘Shield’. Plants were pinched (removal of main shoot to induce both axillary shoots to grow) or non-pinched, and spaced at 56 or 61 cm. All 32 grafted treatments were compared to the grower standard: non-grafted, TL and MFP spaced at 46 cm, which were non-pinched. Fruit quality traits including soluble solids content, pH, lycopene concentration, and citric acid content were recorded for fruit harvested from tomatoes grafted onto ‘Arnold’, ‘Beaufort’, ‘Shield’ and non-grafted TL. The overall effect of grafting TL and MFP onto vigorous rootstocks ‘Arnold’, ‘Beaufort’, and ‘Fortamino’ increased marketable yields per hectare by 24-35% compared to non-grafted grower standards. The rootstock ‘Shield’ did not significantly increase yields with either scion. TL had a more positive response to grafting than MFP. ‘Arnold’, ‘Beaufort’, and ‘Fortamino’ significantly increased TL fruit size, but the fruit size results were not as significantly impacted by graft treatments for MFP. Plants spaced at 56 compared to 61 cm generated similar yields. Pinched plants significantly increased yields over non-pinched plants by 15% in 2018 but did not impact yield in 2017. No consistent difference was observed between pinched and non-pinched plants with regard to fruit size, only plants grafted with ‘Shield’ benefited significantly from being pinched. Soluble solids content, pH, lycopene concentration, and citric acid content were slightly different between grafted and non-grafted plants but unlikely to positively or negatively affect overall perception of fruit quality in tomatoes. A partial budget analysis revealed that grafting with ‘Arnold’ or ‘Beaufort’ consistently increased profits in this low-disease field.